AKIBAT HUKUM PELANGGARAN PRINSIP KEHATI-HATIAN DALAM PEMBERIAN KREDIT OLEH BANK - Oktaviani Gunawan, Liabrintika; Rudy, Dewa Gde; Putrawan, Suatra (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014)
Banking activities in Indonesia its based on some principles like principles ofdemocracy, economic, trust and prudent principle. The purpose of this paper is to findout about precautionary principle in banking legislation. This relates to the provision ofcredit by the banks. As well as to know the legal repercussions for banks that violate theprinciple of prudance. By using normative methods. Prudential arrangements arecommon in banking activities set forth in Article 2 of Law No. 10 Year 1998 onBanking. As a result of violations of the law of the principle of prudence in lendingby banks, can be given legal sanction in the form of criminal sanctions and fines.The issue that been focused on this review is related about managerial andabuse on principal of precaution regarding credit that given by certain bank. Theoutput of this research would reveal that precaution principle management on bankcredit is regulated implicitly on clause 8 and 11 of Law of banking. This impact towardthis precaution principle on crediting is that those who conduct abuse get sanction in(KUHP) or debt sanction.
Keywords: Legal effect, the principle of prudence, the bank lending